Exploring Innovative Structures and Mechanisms in Urban Grassroots Governance: A Network Governance Perspective: Exemplified by the "Five Chiefs System" Grassroots Governance Model in Chongqing, China - Yang, Can (International Journal of Social Sciences and Public Administration, 2024)
This paper examines the "Five Chiefs System" as a grassroots governance model in Chongqing, China, exploring innovative mechanisms in urban grassroots governance from a networked governance perspective. Through a literature review, this study summarizes existing research on innovation in urban grassroots governance, highlighting approaches in technological governance, process re-engineering, and structural research. Building on theories of governance and networked governance, and using the "Five Chiefs System" in Chongqing as a case study, the paper reveals discrepancies between the system and its operational goals as well as the principles of co-governance in practice. Consequently, an analysis of the adaptability of the "Five Chiefs System" and networked governance leads to the exploration of innovative structures and mechanisms for the networked governance of the "Five Chiefs System." This involves developing a decentralized network structure with diverse entities and establishing mechanisms for integration, trust, coordination, and maintenance within networked governance.